Business sustainability performance through sustainability awareness and business work ethics in Islamic institutions - Nunung Ghoniyah; Farikha Amilahaq; Sri Hartono (Cogent Business & Management, 2024)
This study aims to examine the connection between global goals (sustainability) and corporate goals for long-term survival (business sustainability), as well as the role of Islamic business and work ethics in achieving them. 325 responses from employees of Islamic institutions were selected to be examined using the partial least squares (PLS-SEM). The results confirmed that business sustainability could be achieved by implementing Islamic business and work ethics and increasing awareness of sustainable goals (Sustainability Awareness). The results explained that when a company is aware of further goals such as sustainability, it will effectively achieve its ability to survive in the long term, called business sustainability. The originality of this study is providing a clear relationship between sustainability and business sustainability (long-term business goals), while previous research only analyzed sustainability toward business short-term goals.Sustainability goals in an institution or corporation can be seen from two perspectives. First is the corporation's ability to conduct business in the long term, and the second is how an organization encompasses economic, social, and environment-focused investments in its business model and operations. There was much research that put business sustainability as the corporate performance concerning economic, social, and environmental impacts. However, although global sustainability goals are important, corporations still need to assurance their business in the long term. Thus, the authors believe that this global sustainability orientation will not disadvantage the corporation, as this study has proven. In other words, this study tries to present another perspective on the business sustainability of the firm based on stakeholder and sustainability theory. As the author is concerned with Islamic business and ethics, the study focuses on Islamic institutions.
Keywords: 650; Business sustainability performance; long-term business goals; sustainability awareness; Islamic ethics; Islamic institution; primary data